NewConnect - an alternative platform for new innovative companies; NewConnect - alternatywna platforma dla młodych nowatorskich spoĺek - Lucyna Lewandowska (Comparative Economic Research. Central and Eastern Europe, 2010)
The article discusses the attributes of innovation in the context of creating a knowledge-based economy and presents the alternative stock market NewConnect where the small and medium-sized firms may seek funds to finance their innovative projects. NewConnect's functions and goals are shown with respect to capital circulation, stock market training, education and promotion of SMEs aspiring to enter the Warsaw Stock Exchange in the future, as well as the expansion of the financial infrastructure in Poland and the EU. – – W artykule zaprezentowano atrybuty innowacyjnosći w konteksćie kreacji Gospodarki Opartej na Wiedzy oraz alternatywny parkiet NewConnect, stanowiacy szanse pozyskiwania kapitału na nowatorskie projekty przez małe i sŕednie firmy. Wskazano na realizowane funkcje i zadania NewConnect w dziele przepływu kapitału, treningu giełdowego, edukacji i promocji małych i sŕednich spoĺek aspirujacych w przyszłosći do zajecia pozycji na GPW oraz rozbudowy infrastruktury finansowej Polski i Unii Europejskiej.
Keywords: 330